A Metadata Schema Design for Global e-Apostille Processing and a Consortium Blockchain-based Certificate and Verifica-tion Framework for e-Register Service - Yoo, Eunjin; Jung, Geunseong; Cha, Jaehyuk (International Journal of Engineering and Technology, 2019)
Whenever public underlying documents are required for international legal contracts, such as admissions, petitions, and employment, the document often has complicated authentication process. The most exhaustive part is the proof of origin as most countriesâ€™ civil laws do not allow foreign documents as is. Therefore, the foreign applicants should prepare their documents such that they are valid in the destination country. The Apostille Convention helps reduce the complexity of the legalisation process. As an agreement to simplify the certification procedure between countries, it allows them to skip many authentication processes between the Apostille member States.The electronic Apostille program (e-APP) deals with digital documents for the Apostille Convention. However, only a few States support e-APP because of the legislative and procedural differences in electronic documents. For global proliferation of e-APP, the process has to be standardized between States. In this paper, the information for a certificate verification system does not depend on the type of the format of e-Apostille and public documents and design the structure of data sharing and verification system for global e-Register service. The proposed e-Register service consists of a consortium block chain to prevent monopolizing of the data and ensure availability to all.Â